GarageBand 11 Power!: The Comprehensive Recording and Podcasting Guide - Howard, Todd (Course Technology, 2012)
Ready to explore music composition, recording, podcasting, audio/video blogging, remixing/mashing, sound design for video editing or DVD creation, or learning to play the guitar or piano with GarageBand? Great! This book will show you how.